THE MODERATION ROLE OF GENDER ON THE FINANCIAL PERFORMANCE OF BAITUT TAMWIL MUHAMMADIYAH IN INDONESIA - Usamah Usamah (Universitas Airlangga, 2022)
Analyzing the profitability performance of Baitut Tamwil Muhammadiyah (BTM) in Central Java, Indonesia, is the purpose of this study to obtain certainty about the effect of the independent variable on the dependent variable from the data coverage period 2015-2019 using multiple regression analysis. The result indicated that two independentvariables, capital adequacy ratio (CAR) and operating expenses and operating income (BOPO), have relationships with profitability performance except for financial to deposit ratio (FDR) and non-performing finance (NPF). As for moderation variable genders, only the BOPO variable affects ROA significantly. Whereas the FDR, CAR, and NPFvariables are insignificant to the ROA variable. The results of this study are valuable for academics, BTM, and other stakeholders. The results of this study imply that BTM should pay more attention to the role of female managers who benefit BTM in their operational activities. From these results, the authors fill in the limited literature on the role of female managers in BTM in Central Java which has been around for a long time but has not received adequate attention. Due to the limited portion of the role of BTM managers and information on their achievements. This study produces relatively significant implications for BTM to give more roles for women to become managers in BTM for BTM progress.